Bio‐inspired Design and Additive Manufacturing of Soft Materials, Machines, Robots, and Haptic Interfaces. Issue 33 (18th June 2019) - Li, Shuo; Bai, Hedan; Shepherd, Robert F.; Zhao, Huichan
Abstract: Soft materials possess several distinctive characteristics, such as controllable deformation, infinite degrees of freedom, and self‐assembly, which make them promising candidates for building soft machines, robots, and haptic interfaces. In this Review, we give an overview of recent advances in these areas, with an emphasis on two specific topics: bio‐inspired design and additive manufacturing. Biology is an abundant source of inspiration for functional materials and systems that mimic the function or mechanism of biological tissues, agents, and behaviors. Additive manufacturing has enabled the fabrication of materials and structures prevalent in biology, thereby leading to more‐capable soft robots and machines. We believe that bio‐inspired design and additive manufacturing have been, and will continue to be, important tools for the design of soft robots. Abstract : The soft side of robots : This Review gives an overview of current advances in materials with intrinsic softness as well as soft machines, robots, and haptic interfaces. The focus lies on two specific topics: bio‐inspired design and additive manufacturing.